Machine elements in mechanical design - Mott, Robert L.; Tang, John (Pearson Education South Asia Pte Ltd., 2004)
Typically for third year college courses in Machine Design, Design of Machine Elements, and Mechanical Design in Engineering and Engineering Technology programs. This book provides a practical approach to designing machine elements in the context of complete mechanical design. This edition retains many features of the previous edition - exceptional organization, readability, practical approach, sound technical content, extensive appendix, design procedures, example problems, use of computer aids, and use of many examples from commercially available products and systems - yet, has been extensively updated to include new photographs; new design data for some elements; new or revised standards; new end-of-chapter references; listing of internet sites; and some completely new elements.